Role of surface wettability in photoelectrocatalytic oxygen evolution reactions. (April 2022) - Xu, Ruohang; Zhu, Dehang; Du, Kunrong; Cui, Dandan; Feng, Haifeng; Hao, Weichang; Tian, Dongliang; Du, Yi
Abstract: Photoelectrochemical (PEC) water splitting is expected to address challenges in energy crisis and to provide renewable hydrogen energy driven by solar energy and low-power electric energy. Surface wettability of photoanode, which dominates the adsorption and desorption processes of reactants and products, is expected to affect PEC water splitting efficiency. However, its role in PEC reactions and its synergic effects with other intrinsic properties of catalysts in PEC water splitting are still not well understood. Here, we systematically investigated the relationship between the wettability and PEC performance of TiO2 catalysts. The wettability of TiO2 films was successfully modulated by hydrogenation and ultraviolet light irradiation. The hydrophilic TiO2 films showed distinct PEC water splitting performances, which was then found to be determined by the surface wettability and active areas in solid/liquid/gas three-phase interface in reaction. In addition, the wettability also demonstrates a great influence on the stability of the catalyst. This work reveals that water splitting efficiency of PEC catalysts can be significantly improved by tuning surface wettability, which plays an important role in designing and synthesizing highly active catalysts. Graphical abstract: Image 1 Highlights: Wettability of TiO2 films were successfully modulated by hydrogenation and ultraviolet light irradiation. Investigated the relationship between the wettability and photoelectrochemical (PEC) performance of TiO2 catalysts systematically. Comprehensive insights into the role of surface wettability on modulating PEC water splitting over photoanodes.